An Introduction Measure Theory - Tao. Terence (Providence, Rhode Island American Mathematical Society, 2011)
Tao (mathematics, U. of California-Los Angeles) presents a textbook based on his introductory one-quarter graduate course on real analysis, focusing particularly on the basics of measure and integration theory both in Euclidean spaces and in abstract measure spaces. It is meant to precede his 2010 An Epsilon of Room, Volume 1, which introduces the analysis of Hilbert and Banach spaces, point-set topology, and related topics. Together, the two volumes serve as a text for complete first-year graduate course in real analysis. The only prerequisite is undergraduate-level real analysis. Annotation ©2011 Book News, Inc., Portland, OR (booknews.com)
Keywords: Measure theory; Mathematics